Love wave sensors based on gold nanoparticle-modified polypyrrole and their properties to ammonia and ethylene - Šetka, Milena; Potoček, Michal; Král, Zdeněk; Drbohlavová, Jana; Vallejos Vargas, Stella (Elsevier, 2020)
This work presents the fabrication and gas sensing properties of Love wave sensors based on non-modified and gold nanoparticle-modified polypyrrole. Results demonstrate the integration of uniform polypyrrole layers with smooth granular surface and the incorporation of dispersed crystalline gold nanoparticles within the modified layers. Gas sensing tests of the sensors in dry conditions show enhanced sensing performance to ethylene and ammonia for the modified systems as compared to those without modification and those reported in the literature. The effect of humidity proves significant in both systems with the results showing a decrease of sensitivity in humid conditions. Despite this weakness, the relatively facile and scalable fabrication of these sensors, as well as their sensing response at room temperature may be attractive in gas detection systems, in which high humidity levels can be restricted by the use of filter or preconditioning elements.

This work presents the fabrication and gas sensing properties of Love wave sensors based on non-modified and gold nanoparticle-modified polypyrrole. Results demonstrate the integration of uniform polypyrrole layers with smooth granular surface and the incorporation of dispersed crystalline gold nanoparticles within the modified layers. Gas sensing tests of the sensors in dry conditions show enhanced sensing performance to ethylene and ammonia for the modified systems as compared to those without modification and those reported in the literature. The effect of humidity proves significant in both systems with the results showing a decrease of sensitivity in humid conditions. Despite this weakness, the relatively facile and scalable fabrication of these sensors, as well as their sensing response at room temperature may be attractive in gas detection systems, in which high humidity levels can be restricted by the use of filter or preconditioning elements.
Love wave sensors based on gold nanoparticle-modified polypyrrole and their properties to ammonia and ethylene
Keywords: Gas sensors; SAW sensors; Polypyrrole; Gas sensors; SAW sensors; Polypyrrole